Isolation and characterization of indigenous 2,4-D herbicide degrading bacteria from an agricultural soil in proximity of Sauce Grande River, Argentina - Zabaloy, Maria Celina (2014)
Our objective was to isolate and characterize indigenous bacteria able to use 2,4-D as a sole carbon (C) and energy source from an agricultural soil in the Sauce Grande River basin (Argentina). Culturable-dependant and molecular methods combined were used to identify and characterize putatively dominant indigenous degrading bacteria. Physiological traits, chloride release and biomass production showed the degradative capacity of the isolates obtained and high-performance liquid chromatography (HPLC) was used to corroborate the evidence. Degrading genes (tfdA and tfdB) were detected in all isolates, and their restriction fragment length polymorphisms (RFLP) were analyzed. Altogether, our results suggest that agricultural use of 2,4-D at recommended level leads to selection for a copiotrophic degrading population. The dominant genus able to metabolize 2,4-D in this soil was identified as Cupriavidus by 16S rRNA gene sequencing and the RFLP profiles of all isolates resembled that of Cupriavidus necator JMP134, the model organism for 2,4-D degradation. The strain EMA-G showed a remarkable performance in herbicide degradation (100 % removal in less than 1 day) in pure culture and is a favorite candidate for future biodegradation experiments.